George Eliot's Religious Imagination : A Theopoetics of Evolution - Orr, Marilyn, 1950- (Book collections on Project MUSE., 2018)
In this study, Orr attributes to George Eliot an 'incarnational aesthetic' and reads her work in the light of it. Writing, she argues, might be said to have become the novelist's religion and 'its most recognizable tenet was the living out of incarnation'. Here, Orr examines Eliot's works more or less chronologically because of the deeply evolutionary quality to Eliot's career. In a personal sense, she is loathe to repeat herself and, while readers might recognize situations that she is revisiting, she always needs to believe in her own development as a writer. In her letters she repeatedly champions her first stories, for example, largely because they contain "ideas" that she doubts she "can ever embody again." In a broader sense this is an important idea, however, in that her philosophy was grounded in a belief in the idea of progress. Orr engages in close readings of Eliot's writings to demonstrate how deeply the novelist's religious imagination operate in her fiction and poetry.